2022
DOI: 10.3390/su142416415
|View full text |Cite
|
Sign up to set email alerts
|

Microcosm Study on the Potential of Aquatic Macrophytes for Phytoremediation of Phosphorus-Induced Eutrophication

Abstract: Phosphorous (P) is one of the primary nutrients to cause the eutrophication of water bodies. This process leads to algal blooms and anoxic conditions which have consequences in the form of mortality of aquatic animals, and impaired water quality. Aquatic macrophytes could be the promising candidates that can filter P from water contaminated with high levels of nutrients. In the present microcosm research, two types of floating macrophytes, i.e., salvinia floater (Salvinia natans) and water lettuce (Pistia stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In addition, examining the ultimate damage levels in three levels, namely, human health, ecosystem quality, and resources showed that the agricultural sector causes the highest damage. The results of this research are important to meet the sustainable development goals in the era of global warming and climate change [61][62][63][64].…”
Section: Comparison Of the Results Of The Present Study With Other St...mentioning
confidence: 99%
“…In addition, examining the ultimate damage levels in three levels, namely, human health, ecosystem quality, and resources showed that the agricultural sector causes the highest damage. The results of this research are important to meet the sustainable development goals in the era of global warming and climate change [61][62][63][64].…”
Section: Comparison Of the Results Of The Present Study With Other St...mentioning
confidence: 99%
“…Cobalt, nickel, and manganese in lithiumion batteries can also cause hazards, potentially polluting water and ecosystems if they leach from landfills. The inappropriate disposal of batteries are linked to landfill fires or battery recycling facility fires [47].…”
Section: Resultsmentioning
confidence: 99%
“…Salvinia and Pistia are both aquatic plants commonly used in phytoremediation processes and perform differently in phosphate removal efficiency due to species-specific adaptations. Though S. molesta produces a thick mat (Zutshi and Vass, 1971), P. stratiotes can double its biomass within a month, and its long roots (capable of high rhizofiltration) are on average approximately 49 cm in length (Dean et al, 2022). It has recently been reported that S. molesta and P. stratiotes are widely used for the treatment of agricultural, domestic, and industrial wastewater (Akinbile & Yusoff, 2012;Mustafa & Hayder, 2021).…”
Section: Discussionmentioning
confidence: 99%